STRATEGI KOMUNIKASI FRONT OFFICE DALAM MENINGKATKAN MINAT TAMU HOTEL GRAND ZURI PEKANBARU - Saragih, Jackson Truman; ", Nurjanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Hospitality Bussiness competition is blooming nowadays especially in Pekanbaru. More hotels emerging could effect the bussines that direstly influence Tourism Industry. This increases the competition between hotels. Other than facility, service is also one of the many charms of a hotel. The more stars that a hotel have, the more quality the facility and service given by the hotel. As the forefront of service providing, Pekanbaru Grand Zuri’s have communication stategies on incerasing the proclivity rate to visit and providing good Hospitality Service experience from front office. The purpose of this research is to know the front office communication strategy on increasing the proclivity rate, determining communication target, to know the media used in communicating and forms of messages that is used.Researcher used quantitative method with fenomenology approach in this research. Data gathering method are through observation, interview, and documentation. Informant on this research are seven people taken by porposive sampling technique and consist of; 1 HRD officer, 4 front office members, and 2 hotel guest. Reseacher used analysis and interactive model to describe the results of this research and triangulation technique to check the validity of the data.The results of this research shows that the communication stategy implemented by the front officer of Grand Zuri Pekanbaru consist of; communicator stategy, target people, forms of messages, and communication media used. Comunicator strategy is the skill of communicator, experiences, and standart grooming as appealing factor. Target people are blue collar employee and corporate agreement with corporations, Messages to convey are mostly situational, informative and persuasive, and media used are face to face, electronics, social media, and ZHM.